2012
DOI: 10.1111/j.1472-765x.2012.03204.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted:wbeT sequence typing and IS1004 profiling ofVibrio choleraeisolates

Abstract: Aims:  To investigate the molecular basis for serotype variation in Vibrio cholerae O1 and the genetic relatedness amongst different serotypes isolated from 2004 to 2008 in Iran. Methods and Results:  Despite the presence of all three serotypes of V. cholerae O1 (Ogawa, Inaba and Hikojima) in Iran in the last decade, the Inaba strains have been the dominated serotype. Sequence analysis of wbeT determined only a single substitution of G for A at position 295 in all Inaba strains resulting in a replacement of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…T472C was the only nonsynonymous mutation that accounts for a serotype shift in the Inaba strains in 2005, and we experimentally demonstrated the critical role of a serine at this site for the function of RfbT. The same single substitution was also reported in the Inaba strains isolated during different years (2005–2008) in Iran [42] and India [41]. …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…T472C was the only nonsynonymous mutation that accounts for a serotype shift in the Inaba strains in 2005, and we experimentally demonstrated the critical role of a serine at this site for the function of RfbT. The same single substitution was also reported in the Inaba strains isolated during different years (2005–2008) in Iran [42] and India [41]. …”
Section: Discussionsupporting
confidence: 70%
“…Three single nucleotide substitutions and deletion mutations of rfbT have been reported which caused serotype switching due to a frameshift or crucial amino acid residue change in RfbT [22,41,42]. In our study much more mutations are found in the Inaba serotype strains, including single amino acid residue substitutions, frameshifts caused by single nucleotide and short fragment insertions/deletions, and transposition events.…”
Section: Discussionmentioning
confidence: 51%
“…Accession number JX565662) where the phenotype is reported as Inaba. We have found the same mutation in additional Inaba strains in our strain collection [17] and this specific wbeT mutation has been reported also by other groups as associated with the Inaba serotype [18] , [19] . No other mutations associated with a Hikojima phenotype have been defined.…”
Section: Discussionsupporting
confidence: 85%
“…Regional cholera outbreaks from 2005 through 2009 in Iran were due to Inaba strains that have been developed from their prevailing Ogawa (before 2005) by point mutation in O‐antigen‐encoding cluster ( wbe T) (Sharifnia et al . ). Furthermore, sequence analysis revealed the presence of two ctxB genotypes among V. cholerae strains isolated from recent outbreaks (2004–2009) (Aliabad et al .…”
Section: Discussionmentioning
confidence: 97%